2015
DOI: 10.1589/jpts.27.2863
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of Zumba<sup>®</sup> performed in a virtual environment using XBOX Kinect

Abstract: [Purpose] This study evaluated the acute cardiovascular responses during a session of Zumba® Fitness in a virtual reality environment. [Subjects] Eighteen healthy volunteers were recruited. [Methods] The following cardiovascular variables: heart rate, systolic blood pressure, diastolic blood pressure, and double product were assessed before and after the practice of virtual Zumba®, which was performed as a continuous sequence of five choreographed movements lasting for 22 min. The game Zumba Fitness Core®, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
2
15
0
7
Order By: Relevance
“…11 The videogames that adopt physical interaction with the user are called "exergames" 12,13 and provide body motion as a form of exercise. 14 Physical exercise influences physical fitness, whose components include flexibility, muscle strength, cardiorespiratory endurance and body composition.…”
Section: -629mentioning
confidence: 99%
“…11 The videogames that adopt physical interaction with the user are called "exergames" 12,13 and provide body motion as a form of exercise. 14 Physical exercise influences physical fitness, whose components include flexibility, muscle strength, cardiorespiratory endurance and body composition.…”
Section: -629mentioning
confidence: 99%
“…16 These characteristics are crucial for increasing motivation and self-efficacy, as well as for possibly keeping people physically active. 17 Previous studies have shown that exergame interventions are able to improve the following: physical activity levels, 18 the performance of daily activities, 19,20 heart rate, [21][22][23][24][25] oxygen consumption, 21,23,25 and energy expenditure in various populations 21,23,25,26 ; improvements in body composition in children 27 ; and postural balance 28 and cognitive function in older adults. 29 Moreover, it has already been demonstrated that a single session of a dance exergame reduced anxiety levels in young adult women.…”
Section: Introductionmentioning
confidence: 99%
“… Neves et al (2015) investigated the acute cardiovascular responses during a session of the game Zumba Fitness Core ® performed with XBOX 360 and observed a significant increase of HR immediately after the session. Graves et al (2010) compared the physiological cost among adolescents, young, and older adults during a game with a joystick, Wii® Fit activities (yoga, muscle conditioning, balance, and aerobics), and brisk treadmill walking and jogging and found that energy expenditure and HR of Wii® Fit activities were greater than joystick games, but lower than treadmill exercise and that the Wii® elicited moderate intensity activity.…”
Section: Introductionmentioning
confidence: 99%